Suppression of the high endogenous levels of plasma FSH in infertile men are associated with improved Sertoli cell function as reflected by elevated levels of plasma inhibin B - Foresta, C.; Bettella, A.; Spolaore, D.; Merico, M.; Rossato, M.; Ferlin, A. (Human reproduction (Oxford), 2004)
BACKGROUND. In vitro continuous stimulation of Sertoli cells with FSH leads to a desensitization of these cells to FSH action. To evaluate the presence of a desensitization of FSH receptor on Sertoli cells in vivo, we performed a controlled clinical study in 97 men affected by severe oligozoospermia. METHODS. On the basis of FSH and inhibin B plasma concentrations, these subjects were divided into three groups: group A, 33 subjects with high FSH and low inhibin B plasma levels; group B, 32 subjects with high FSH plasma levels and inhibin B concentrations at the lower limit of the normal range; and group C, 32 subjects with normal FSH and inhibin B plasma levels. Patients with high FSH plasma levels (groups A and B) were prospectively randomized into two subgroups, called A1, A2, B1 and B2. Patients of groups A1 and B1 were treated with a GnRH agonist, leuprolide acetate, to induce a hypogonadotrophic state and then were treated with recombinant human FSH (r‐hFSH; 100 IU/day) and hCG (2000 IU/twice a week) for 2 months. Subjects of groups A2, B2 and C were treated only with r‐hFSH for the same period. RESULTS. In patients of group A1, inhibin B remained unmodified during the whole period of study, whereas in subjects of group B1, we observed a significant reduction of this hormone during the hypogonadotrophic period and then an increase of inhibin B plasma levels that were higher that those observed before therapy. In patients of groups A2 and B2, FSH treatment did not induce a significant increase in inhibin B concentrations. In patients of group C, FSH induced a significant increase in inhibin B plasma levels. CONCLUSIONS. In infertile men, suppression of the high endogenous levels of plasma FSH associated with much lower exogenous FSH levels is able to evoke higher inhibin B production, which may indicate improved Sertoli cell function and the possibility that this could have a positive effect on spermatogenesis.